ERROR CORRECTION MODEL ANALYSIS OF THE DETERMINANT OF STABILITY OF FINANCIAL SYSTEM IN INDONESIA - Muhammad Rismawan Ridha (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2020)
The current condition of economic openness is both an opportunity and a challenge that must be faced wisely by the government. Liberalization and economic integration will have an impact on financial market liberalization, which is highly vulnerable to create crisis in a banking system. This study aims to analyze the factors that influence the stability of the financial system in Indonesia by using the Error Correction Model (ECM). The variables used in this research is Capital Banking Credit sourced from Statistics Indonesia (BPS) and Exchange Rate, Inflation, and Money Supply sourced from the International Monetary Fund (IMF) between 2010 and 2015. The results of the study show that; 1) ECT coefficient which has negative and significant value explains that the model is valid. 2) Inflation significantly affects the stability of the financial system in Indonesia in the long and short term